Revised world catalogue of Eucopina, Eucosma, Pelochrista, and Phaneta (Lepidoptera: Tortricidae: Eucosmini) - Gilligan, Todd M.; Wright, Donald J. (Zootaxa, 2013)
A revised world catalogue of Eucopina, Eucosma, Pelochrista, and Phaneta is provided. Assignment to genus is based on generic redescriptions by Gilligan et al. (2013). A total of 709 names (including subspecies and synonyms) are listed, including 251 new combinations and 52 revised combinations.